PDEODE-WEB-BASED Blended Learning As 21st Century Learning Development Solutions - Zulfarina Zulfarina; Tuti Mailani; Wan Syafii (Universitas Riau, 2021)
The purposes of this study are to develop a PDEODE-WEB based Blended Learning model, and determine the quality of the developed PDEODE-WEB based Blended Learning model on digestive system material in terms of validity, practicality, and effectiveness. This study employed a 4D development research (R&D) which consists of Define, Design, Development, and Disseminate. The results showed that the validation of material and media experts for content validation was 3 with very important categories. Analysis from a learning expert for the construction validation category obtained 4.03 with the very good category. The results of the limited trial obtained a score of 81.47 in the good category and the practicality test obtained 90.6 which could be categorized as very practical. The effectiveness test was carried out obtained the N-Gain of 0.6 with the medium category. The PDEODE-WEB Blended Learning model that was developed meets the criteria of validity, practicality, and effectiveness as a solution for the development of learning in the 21st century.